Health-Promoting Behaviors and Experiences of Korean Oceangoing Seafarers: A Mixed-Methods Study - Yun-Seo Jung; Hyoung Sook Park (Journal of Fundamental Nursing Science, 2026)
Purpose: This study aimed to identify factors associated with health-promoting behaviors among Korean oceangoing seafarers using a quantitative approach and to explore their experiences of health-promoting behaviors using a qualitative approach. Methods: A mixed-methods design was used. Quantitative data were collected from 132 Korean oceangoing seafarers, all of whom were male, with a mean age of 48.4 years. Structured questionnaires were used to measure health-promoting behaviors, hardiness, self-efficacy, and social support. Hierarchical multiple regression analysis was conducted to identify factors associated with health-promoting behaviors. Qualitative data were obtained through two focus group interviews with eight seafarers and analyzed using content analysis. Results: The mean score for health-promoting behaviors was 2.23 on a 4-point scale, indicating relatively low engagement in health-promoting behaviors. Hardiness, self-efficacy, education, exercise, and job stress explained 56.5% of the variance in health-promoting behaviors, with hardiness showing the strongest association. Qualitative analysis identified three themes reflecting seafarers' health-promoting behaviors: difficulties in maintaining health in the shipboard environment, health management and institutional support for protecting seafarers' health, and habituation of health-related behaviors during long voyages. Conclusion: These findings highlight the importance of psychological resources, including hardiness and self-efficacy, in sustaining health-promoting behaviors among oceangoing seafarers. Tailored nursing interventions and health promotion programs that reflect the unique occupational environment of maritime workers are needed to support healthier lifestyles among seafarers.